2015
DOI: 10.17113/ftb.53.03.15.3931
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Anthocyanin Content in Sour Cherry Juice During Heat Treatment

Abstract: Sour cherry juices made from two sour cherry cultivars (Érdi bőtermő and Kántorjánosi 3) were investigated to determine their total anthocyanin content and half-life of anthocyanins during heat treatment at different temperatures (70, 80 and 90 °C) for 4 h. Before the heat treatment, Érdi bőtermő juice had higher anthocyanin concentration (812 mg/L) than Kántorjánosi 3 juice (513 mg/L). The greatest heat sensitivity of anthocyanins was measured at 90 °C, while the treatments at 80 and 70 °C caused lower therma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…This slight increase may be due to the liberation of pigment components from the shells of berries by wall and membrane disruption. On the contrary, heating–cooling (step 3) seems to cause some slight but not statistically significant pigment loss, which is in accordance with literature as several studies reported sensitivity of anthocyanins during thermal treatment (Kirca et al ., ; Castaneda‐Ovando et al ., ; Patras et al ., ; Turfan et al ., ; Ioannou et al ., ; Szalóki‐Dorkó et al ., ). Interestingly, no significant changes were observed in average TA content as a result of first enzymatic treatment (step 4) where the primary pectin breakdown was performed and similarly after the following mash pressing (step 5); however, a slightly increasing trend resulted by steps 4 and 5 can be seen in the case of Samocco.…”
Section: Resultsmentioning
confidence: 97%
“…This slight increase may be due to the liberation of pigment components from the shells of berries by wall and membrane disruption. On the contrary, heating–cooling (step 3) seems to cause some slight but not statistically significant pigment loss, which is in accordance with literature as several studies reported sensitivity of anthocyanins during thermal treatment (Kirca et al ., ; Castaneda‐Ovando et al ., ; Patras et al ., ; Turfan et al ., ; Ioannou et al ., ; Szalóki‐Dorkó et al ., ). Interestingly, no significant changes were observed in average TA content as a result of first enzymatic treatment (step 4) where the primary pectin breakdown was performed and similarly after the following mash pressing (step 5); however, a slightly increasing trend resulted by steps 4 and 5 can be seen in the case of Samocco.…”
Section: Resultsmentioning
confidence: 97%
“…This is also reflected in the results of our study, where the stability of peonidin > cyanidin > petunidin > delphinidin decreases with an increasing number of substituents. Therefore, the inter-genotype differences in anthocyanins are supposed to be a significant factor in their thermal degradation (Szalóki-Dorkó et al 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Szalóki-Dorkó [24] suggested also a decrease of the anthocyanin content ofÉrdi bőtermő juices, from 812 to 501 mg/L at 90°C after 240 min of heating. Degradation was lower at 80°C, and the treatment for 4 h at this temperature resulted in 29% loss of total anthocyanin content compared to the original levels found in fresh juice.…”
Section: E Influence Of Ermal Treatment On Tac and Dpphmentioning
confidence: 94%